The influence of breastfeeding father and mother's self-efficacy on the success of exclusive breastfeeding in mother's having a baby in Jorlang Huluan Village - Sianturi, Marta Imelda; Sinaga, Elvipson; Hutasoit, Dessy Meilani; Togatorop, Linawati (Institute of Computer Science (IOCS), 2024)
The success of providing exclusive breastfeeding in Jorlang Huluan Village, Pamatang Sidamanik District, Simalungun Regency is still low. The low level of exclusive breastfeeding in Jorlang Huluan Village is related to breastfeeding fathers and mothers' self-efficacy. This study aims to determine the influence of breastfeeding fathers and self-efficacy on the success of exclusive breastfeeding for mothers with babies in Jorlang Huluan. The type of research used is analytical survey research with a cross sectional design. The population in this study were all mothers who had babies 7-12 months in Jorlang Huluan Village, totaling 52 people and the research sample used total sampling. Data were collected using primary and secondary data and analyzed using the Multiple Logistic Regression chi statistical test with a confidence level of 95%. The results of the research show that there is an influence of breastfeeding fathers and self-efficacy on the success of exclusive breastfeeding in mothers who have babies 7-12 months in Jorlang Huluan Village. It is recommended that husbands of respondents in Jorlang Huluan Village seek information about Exclusive Breastfeeding and that health workers in Jorlang Huluan Village need to increase mothers' understanding of Exclusive Breastfeeding and increase family support in efforts to increase Exclusive Breastfeeding.